Comparing the Determinants of Western and Chinese Development Finance Flows to Africa - David G. Landry (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2018)
This paper by David G. Landry explores whether various institutional indicators among African countries impact their development finance from China and Western countries differently. This research is the first to explicitly compare the determinants of the value of Chinese and Western development finance received by other countries. It finds that bilateral trade relations and UN voting alignment have a stronger impact on China's development finance than that of Western countries. The research also finds that institutional quality plays a much stronger role in predicting Western development finance than that of China, as China appears to disregard institutional quality in its allocation of development finance.
Keywords: 330